Penyuluhan Antimicrobial Resistance Awareness (AMIRA) Sebagai Upaya Pencegahan Dan Pengendalian Resistensi Antimkroba Dengan Pendekatan One Health Pada Ibu – Ibu PKK - Sri Rahayu Rubiyanto; Chairil Hana Mustofa; Rahmatika D N (Universitas Muhammadiyah Klaten, 2025)
The increasing number of cases of Antimicrobial Resistance (AMR) in living things is a problem of high health care costs and everything related to the progress of sustainable development (SDGs) in 2030. Uncontrolled antimicrobial resistance (AMR) is very detrimental and not only to global health problems, but also financially, food security, environmental welfare, and socio-economic development. In the case of health, antimicrobial resistance (AMR) which occurs everywhere and can attack anyone regardless of age at the national, regional, and global levels if left unchecked, will cause death, disability, and increased health care costs. Knowledge about AMR is important to be disseminated and understood by the community. There are records from the Brangsong I Health Center for the last 5 years, the level of antibiotic use in Sidorejo Village has reached 90%, besides that there have also been 116 cases of tuberculosis, some of which ended in death. The PKK mothers of Sidorejo Village have high enthusiasm to understand and gain knowledge about AMR to the wider community. Based on this potential, Sidorejo Village has become a pioneer in caring for health through the Antimicrobial Resistance (AMR) counseling program. This program is designed with a discussion flow for counseling programs, preparation, and counseling on AMR. The program will support the realization of a community that cares about AMR, prevents infectious diseases caused by microbes that are difficult to cure and becomes a pioneer in caring about AMR.